Isolation, purification and evaluation of anticancer principle from Zingiber zerumbet - Rahman, Heshu Sulaiman; Othman, Hemn Hassan; Abdullah, R.; Chartrand, Max Stanley; Allaudin, Zeenathul Nazariah; Ajdari, Zahra; Hosseinpour, Mahnaz; Abdul Samad, Nozlena (UPM-MAKNA Cancer Research Laboratory, Institute of Bioscience, 2014)
The Zingiberaceae family is found in tropical and subtropical areas, with approximately 161 species from 18 genera of this family found in Peninsular Malaysia. Zingiber zerumbet (L.) Smith tree belonging to this family is an edible ginger, originating in South-East Asia, and has been cultivated for thousands of years as a spice and for medical purposes. The aim of this study is to isolate the active principle from extracted essential oil of fresh Zingiber Zerumbet rhizomes by steam-hydrodistillation method. In addition, to determine the purity of this active compound using validated reverse phase high performance liquid chromatography (RP-HPLC). Moreover, the antiproliferative effects of this active principal on various human cancerous and noncancerous cell lines at concentrations of 1 to 100 μg/mL were quantified by MTT assay. As a result, colorless zerumbone (ZER) crystals about 1.3 g/kg as an active principal were extracted from the essential oil of fresh Z. Zerumbet rhizomes. The purity of ZER crystals were shown to be (99.96%). Simultaneously, ZER exhibited significant (P < 0.05) inhibitory effects towards various human cancerous cell lines, while not affected noncancerous cell lines. In conclusion, ZER is suggested to be further developed into a safe therapeutic compound for the treatment of various human cancers.